2020
DOI: 10.1002/ags3.12388
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results of a randomized controlled trial comparing neoadjuvant Adriamycin, cisplatin, and 5‐fluorouracil vs docetaxel, cisplatin, and 5‐fluorouracil followed by surgery for esophageal cancer (OGSG1003)

Abstract: Aim The aim is to report the long‐term outcomes of preoperative cisplatin and fluorouracil plus docetaxel (DCF) vs Adriamycin (ACF) for resectable esophageal squamous cell carcinoma (ESCC). Previously, this trial showed that DCF is associated with prolonged recurrence‐free survival (RFS). Methods Patients were randomly assigned to two cycles of ACF (35 mg/m2 of Adriamycin, 70 mg/m2 of cisplatin intravenously on day 1, and 700 mg/m2 of fluorouracil infusion for 7 days) every 4 weeks or DCF (70 mg/m2 of docetaxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…It is worth noting that no significant difference between DCF and ACF was found in OS; a possible reason is that the follow-up period was too short (34.5 months). Therefore, a follow-up study was conducted to assess the long-term outcomes and analyze the primary endpoint, RFS, as well as secondary endpoints such as OS and recurrence patterns [33]. Consistent with the preliminary results, this study confirmed a better 5-year RFS for DCF (59.9% vs. 40.7%).…”
Section: Progression and Optimization In The Treatment Protocols Of Nctsupporting
confidence: 79%
“…It is worth noting that no significant difference between DCF and ACF was found in OS; a possible reason is that the follow-up period was too short (34.5 months). Therefore, a follow-up study was conducted to assess the long-term outcomes and analyze the primary endpoint, RFS, as well as secondary endpoints such as OS and recurrence patterns [33]. Consistent with the preliminary results, this study confirmed a better 5-year RFS for DCF (59.9% vs. 40.7%).…”
Section: Progression and Optimization In The Treatment Protocols Of Nctsupporting
confidence: 79%
“…The postoperative recurrence pattern in patients with preoperative DCF has been analyzed in the OGSG1003 phase Ⅱ trial in 162 patients with resectable esophageal cancer in preoperative DCF or CF plus adriamycin. This study showed that DCF had significantly higher control rates of distant recurrence than CF plus adriamycin (21% vs. 32%, respectively) [12]. In the present study, we compared preoperative CF + RT and DCF for advanced ESCC retrospectively.…”
Section: Discussion/conclusionmentioning
confidence: 83%
“…The DCF regimen is a beneficial preoperative treatment with higher pathological response and better survival [11][12][13][14][15][16][17]. The postoperative recurrence pattern in patients with preoperative DCF has been analyzed in the OGSG1003 phase Ⅱ trial in 162 patients with resectable esophageal cancer in preoperative DCF or CF plus adriamycin.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first failure sites were categorized as local, regional nodal, or distant. In previous studies of locally advanced esophageal cancer patients who underwent chemoradiation followed by esophagectomy, the rates were 4.5-67% local, 10-57.9% regional nodal, and 21-32% distant failures [23][24][25][26]. Local failure was correlated with fewer lymph nodes (LNs) assessed and close/positive margins.…”
Section: Discussionmentioning
confidence: 99%